First Principle Calculations for Silver Halides AgBr, AgCl, and AgF - Akram H. Taha (Koya University, 2021)
Density functional theory (DFT) coupled with ) method are carried out to calculate the electronic structures of AgX (X; Br, Cl, and F). The effect of hybridizing between 4d orbital of Ag element and the p orbitals of the X in the valence band plays a very important role in the total density of states configuration. The electronic structure has been studied and all results were compared with the experimental and theoretical values. The importance of this work is that there is insufficient studies of silver halides corresponding the great importance of these compounds. Almost all the results were consistent with the previous studies mentioned here. We found the band gap of AgX to be 2.343 eV, 2.553 eV, and 1.677 eV for AgBr, AgCl, and AgF respectively which are in good agreement with the experimental results.